Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Deriving the Bateman equation of Nuclear Decay Chains

  1. Mar 13, 2007 #1
    1. The problem statement, all variables and given/known data

    Derive Bateman equation for a decay chain
    a->b->c->d where each decays with a given mean life let decay constant be L, where L=1/mean life
    Na(0)=No, Nb(0)=Nc(0)=Nd(0)=0

    2. Relevant equations

    Want to derive Nb(t)={(No)(La)/(Lb-La)}*{exp[-La*t]-exp[-Lb*t]}
    extend for Nc(t)

    3. The attempt at a solution

    dNa(t)/dt=-La*Na(t)
    Na(t)=No*exp[-La*t]

    dNb(t)/dt=-Lb*Nb(t)+LaNa(t)
    dNb(t)/dt=-Lb*Nb(t)+La{No*exp[-La*t]}

    this is a none homogenous differential equation. I can't find a way to solve it.

    dNc(t)/dt=-Lc*Nc(t)+LbNb(t)

    I'm really not sure where to go from here.

    If anyone could lend a hand it would be greatly appreciated.
     
  2. jcsd
  3. Mar 14, 2007 #2

    Dick

    User Avatar
    Science Advisor
    Homework Helper

    Ok, so what you are really asking is how to solve y'(t)+L*y(t)=f(t). You know the homogenous solution is exp(-L*t). Guess the solution will be of the form y(t)=g(t)*exp(-L*t). Put this guess into your original equation and get:

    g'(t)*exp(-L*t)-L*g(t)*exp(-L*t)+L*g(t)*exp(-L*t)=f(t).

    So g'(t)=exp(L*t)*f(t) and you can just integrate to get g(t).
     
Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook

Have something to add?
Similar Discussions: Deriving the Bateman equation of Nuclear Decay Chains
  1. Nuclear Decay (Replies: 2)

  2. Nuclear Decay (Replies: 1)

  3. Nuclear Physics decay (Replies: 0)

Loading...